Biological activities of extracts and compounds from Thai Kae-Lae (Maclura cochinchinensis (Lour.) Corner) - Lapamas Rueankham; Pawaret Panyajai; Aroonchai Saiai; Methee Rungrojsakul; Singkome Tima; Sawitree Chiampanichayakul; Kankanit Yeerong; Suvimol Somwongin; Wantida Chaiyana; Pornngarm Dejkriengkraikul; Siriporn Okonogi; Trinnakorn Katekunlaphan; et al. (BMC, 2023)
Abstract Background and aims The purpose of this study was to investigate the biological properties of Kae-Lae (Maclura cochinchinensis (Lour.) Corner), a traditional medicinal plant used in Ayurvedic recipes in Thailand. To achieve this objective, heartwood samples were collected from 12 sources across Thailand. Fractional extracts (n-hexane, ethyl acetate, and ethanol) and the dominant compounds (morin, resveratrol, and quercetin) were examined for their abilities on cytotoxicity, antioxidant, anti-inflammation, and antileukaemic activity (Wilms' tumour 1 protein was used as a well-known biomarker for leukaemic cell proliferation). Methods The study used MTT to assess cytotoxicity in leukaemic cells (K562, EoL-1, and KG-1a). Antioxidant activities were evaluated using ABTS, DPPH, and FRAP assays. The anti-inflammatory activity was investigated by detecting IL-2, TNF-α, and NO using appropriate detection kits. Wilms' tumour 1 protein expression was measured by Western blotting to determine the anti-leukaemic activity. The inhibition of cell migration was also analyzed to confirm anticancer progression. Results Among the tested extract fraction, ethyl acetate No. 001 displayed strong cytotoxicity specifically in EoL-1 cells, while n-hexane No. 008 demonstrated this effect in three cell lines. Resveratrol, on the other hand, displayed cytotoxicity in all the tested cells. Additionally, the three major compounds, morin, resveratrol, and quercetin, exhibited significant antioxidant and anti-inflammatory properties. In particular, resveratrol demonstrated a noteworthy decreased Wilms' tumour 1 protein expression and a reduction in cell proliferation across all cells. Moreover, ethyl acetate No. 001, morin, and resveratrol effectively inhibited MCF-7 cell migration. None of these compounds showed any impact on red blood cell haemolysis. Conclusion Based on these findings, it can be concluded that Kae-Lae has promising chemotherapeutic potential against leukaemic cells, with fractional extracts (ethyl acetate and n-hexane) and resveratrol exhibiting the most potent cytotoxic, antioxidant, anti-inflammatory, and anti-cell migration activities.